Pengembangan E-modul Berintegrasi Al-Qur’an Menggunakan Software Sigil pada materi Usaha dan Energi Fisika Kelas X SMA/MA - Wahyu Supriati; Venny Haris (Edusainstika: Jurnal Pembelajaran MIPA, 2021)
The background of this research is the balance between intellectual and spiritual abilities which causes the younger generation to tend to prioritize general knowledge that triggers current technological developments and ignore religious knowledge, so that there is an imbalance between intellectual and spiritual. At the time of the COVID-19 pandemic, there was a lack of learning resources used by educators to teach, so that students had difficulty understanding the materials and concepts provided by educators. Therefore, it is necessary to provide learning resources that students can use independently and attract students' interest in learning. In this case, the researcher designed an e-module using Sigil Software on the material of work and energy. This study uses the type of 4-D development (define), design (design), develop (development), and desseminate. This research instrument uses a validation sheet, a practical sheet and a test instrument. This e-module was validated by 3 validators, namely 2 physics lecturers, 1 lecturer in Al-Quran science. In the process of practicality and effectiveness of the physics e-module, 34 students of class X IPA 1 SMA SMAN 1 Kinali were tested. The results showed that: 1) the results of the validity of the Al-Qur'an integrated e-module using Sigil Software obtained were 82.01% with a very valid category, 2) the practical results of the Al-Qur'an integrated e-module Using Sigil Software were obtained from the results of the student response questionnaire that is 91% while the results of the teacher response questionnaire are 87.16% with a very practical category, and the increase in pretest and posttest scores is analyzed using the N-gain test, which is 0.80 in the high category. With this, it can be concluded that the e-module integrated with the Qur'an using Sigil Software is valid, practical, and effective